East-west advancement flap: a useful tool to reconstruct nasal tip defects - Katherine Santacoloma; Barbara Ciraudo; Marcela Duarte Benez Miller; Guillermo Loda (Sociedade Brasileira de Dermatologia (SBD), 2021)
The reconstruction of nasal defects secondary to non-melanoma skin cancer represents a surgical challenge, especially in the nasal tip, due to its limited local laxity and possible asymmetries.There are multiple techniques to perform this closure, but most are flaps from distant locations that can lead to less aesthetic results. We present two cases of basal cell carcinoma on the nasal tip, where reconstruction with the east-west advancement flap was performed after tumor excision, with a modification of the flap in one of the patients, obtaining a good structural and aesthetic result.